2018
DOI: 10.7567/jjap.57.08rd05
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of GaAs//indium tin oxide/Si junctions for III–V-on-Si hybrid multijunction cells

Abstract: The electrical properties of GaAs//indium tin oxide (ITO)/Si junctions fabricated by surface-activated bonding (SAB) are investigated with emphasis on their dependence on the temperature of postbonding annealing. The current-voltage (I-V) characteristics of n + -GaAs//ITO/p + -Si and n + -GaAs//ITO/n + -Si junctions without annealing are linear. Those of p + -GaAs//ITO/p + -Si and p + -GaAs//ITO/n + -Si junctions without annealing are nonlinear. Although the interface resistance of all the junctions increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In contrast, the p-GaAs=ITO==ITO=n-Si exhibited Schottky-like characteristics with a high interface resistance. A value of 7.9 × 10 −2 Ω•cm 2 was reported 28) for n-GaAs==ITO=Si without annealing, following the formation of a thicker ITO layer only on the n-Si substrate (compared with the thin 20-nm ITO layer in the present work). However, it was reported that this thicker layer could potentially degrade the performance of a solar cell, because the refractive-index difference between ITO and Si might increase the reflectivity, limiting the incident light reaching the Si subcell.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In contrast, the p-GaAs=ITO==ITO=n-Si exhibited Schottky-like characteristics with a high interface resistance. A value of 7.9 × 10 −2 Ω•cm 2 was reported 28) for n-GaAs==ITO=Si without annealing, following the formation of a thicker ITO layer only on the n-Si substrate (compared with the thin 20-nm ITO layer in the present work). However, it was reported that this thicker layer could potentially degrade the performance of a solar cell, because the refractive-index difference between ITO and Si might increase the reflectivity, limiting the incident light reaching the Si subcell.…”
supporting
confidence: 56%
“…However, these structures are difficult to fabricate using conventional methods such as vapor-phase epitaxy and high-temperature fusion bonding, owing to the differences in the thermal expansion coefficients and lattice constants between GaN and GaAs or between GaAs and Si. Roomtemperature wafer bonding [20][21][22][23][24][25][26][27][28] using an Ar ion beams [21][22][23][24][25] is a promising approach, as this technique allows the bonding of materials with different coefficients of thermal expansion and lattice constants.…”
mentioning
confidence: 99%
“…Concentration depth profiles of O, Ga, and As atoms obtained using XPS measurements suggest that the oxidation markedly occurs at GaAs//ITO interfaces annealed at temperatures higher than 200 °C, which is consistent with the dependence of resistance in GaAs//ITO/ Si junctions on the temperature. 96) These results suggest that annealing brings about the reaction between GaAs and ITO layers and causes the degradation of the electrical properties of GaAs//ITO interfaces. Low temperature process technologies are essential to make full use of ITO as an intermediate layer in III-V-on-Si MJ cells.…”
Section: Resistance Across Bonding Interfaces In Mj Cellsmentioning
confidence: 93%
“…Representatively, RPD ITO was applied in the silicon-based multijunction cells and the series resistance was effectively reduced due to its high quality and low process-induced damage. 27 To evaluate the damage degree of different ITO deposition methods, the interface defect density (D it ) at the Si/SiO 2 interfaces was quantitatively analyzed by depositing the same thickness films. The D it in the RPD ITO process is about 1 × 10 10 cm −2 eV −1 , far less than that in the magnetron sputtering method (7.5 × 10 10 cm −2 eV −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a soft method, RPD has been applied in the preparation of TCO films in the fabrication of solar cells and was repeatedly reported to play an active role in preventing damage to the as-deposited function layer films. Representatively, RPD ITO was applied in the silicon-based multijunction cells and the series resistance was effectively reduced due to its high quality and low process-induced damage . To evaluate the damage degree of different ITO deposition methods, the interface defect density ( D it ) at the Si/SiO 2 interfaces was quantitatively analyzed by depositing the same thickness films.…”
Section: Introductionmentioning
confidence: 99%